2020
DOI: 10.1155/2020/2980954
|View full text |Cite
|
Sign up to set email alerts
|

High-Serum Angiopoietin-Like Protein 3 Levels Associated with Cardiovascular Outcome in Patients with Coronary Artery Disease

Abstract: Background. Angiopoietin-like protein 3 (ANGPTL3) plays a pivotal role in lipid metabolism and angiogenesis, and there is growing interest regarding the association between ANGPTL3 and coronary artery disease (CAD). This study aims to investigate whether ANGPTL3 levels can be used to predict the future occurrence of major adverse cardiovascular events (MACEs) in patients with CAD. Methods. Overall, 90 patients with CAD were enrolled between January and December 2012. The study’s primary endpoint was incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…66 Also, in a prospective cohort study in which 90 patients with ASCVD were enrolled, the relationship between baseline serum ANGPTL3 levels and the risk of major adverse cardiovascular events (MACEs) was explored: not only did patients with ASCVD have higher plasma levels of ANGPTL3, but circulating ANGPTL3 proteins were independently related to the higher risk of MACEs among subjects with ASCVD. 84 Similarly, Li et al 87 showed that in patients with obstructive sleep apnoea syndrome, elevated levels of ANGPTL3 predicted a higher risk of ASCVD. The intima-media thickness (IMT) of carotid arteries (CA) and IMT-femoral arteries (FA) are two metrics for estimating the extent of atherosclerosis.…”
Section: Circulating Angptl3 As a Potential Biomarker Of Ascvdmentioning
confidence: 98%
See 3 more Smart Citations
“…66 Also, in a prospective cohort study in which 90 patients with ASCVD were enrolled, the relationship between baseline serum ANGPTL3 levels and the risk of major adverse cardiovascular events (MACEs) was explored: not only did patients with ASCVD have higher plasma levels of ANGPTL3, but circulating ANGPTL3 proteins were independently related to the higher risk of MACEs among subjects with ASCVD. 84 Similarly, Li et al 87 showed that in patients with obstructive sleep apnoea syndrome, elevated levels of ANGPTL3 predicted a higher risk of ASCVD. The intima-media thickness (IMT) of carotid arteries (CA) and IMT-femoral arteries (FA) are two metrics for estimating the extent of atherosclerosis.…”
Section: Circulating Angptl3 As a Potential Biomarker Of Ascvdmentioning
confidence: 98%
“…Evolving evidence supports the contention that ANGPTL3 plays an important role in lipid metabolism. Several studies revealed that plasma ANGPTL3 levels were positively associated with circulating LDL‐C and HDL‐C, indicating that circulating ANGPTL3 proteins could be a potential ASCVD biomarker 41,84‐86 . In a population‐based study, patients in the lowest tertile of plasma ANGPTL3 levels showed a reduced ASCVD risk by 29% compared with those in the highest tertile 66 .…”
Section: Circulating Angptl3 As a Potential Biomarker Of Ascvdmentioning
confidence: 99%
See 2 more Smart Citations
“…Body weight and height (Tanita WB-380, Tanita Corporation, Tokyo, Japan) were recorded to the nearest 0.5 kg and 0.5 cm, respectively. Body mass index was calculated as the weight in kilograms divided by the height in meters squared [17,18].…”
Section: Anthropometric Analysismentioning
confidence: 99%